'Isolated anti‐HBc' in blood donors: Significance after implementation of single‐unit nucleic acid amplification test?. (21st August 2019) - Tiwari, Aseem Kumar; Dara, Ravi C.; Arora, Dinesh; Aggarwal, Geet; Sharma, Jyoti; Chandnani, Madhu; Bhardwaj, Gunjan
Abstract : Background: Though seropositivity for anti‐HBc is high in India, neither anti‐HBc nor single‐unit NAT (ID‐NAT) is mandatory. Approximately 10% of blood transfusion services in India employ anti‐HBc (Total) testing, and approximately 50% of these also do NAT testing routinely. Adding anti‐HBc test to transfusion‐transmissible disease testing for screening donated blood remains controversial, especially after introduction of ID‐NAT testing in several centres. Materials and methods: Prospective study was undertaken where anti‐HBc positive, HBsAg negative and ID‐NAT negative donor samples were investigated for HBeAg, anti‐HBe and anti‐HBs. Isolated anti‐HBc (anti‐HBc positive, HBeAg negative, anti‐HBe negative and anti‐HBs negative) samples were analysed by a sensitive polymerase chain reaction (RT‐PCR). Results: 955/14296 (7·6%) samples were anti‐HBc repeat reactive. While none of these were reactive for HBeAg, 696 samples were in possible convalescent phase (anti‐HBe positive) or resolution phase (anti‐HBs positive). A total of 259 were isolated anti‐HBc positive, and there were two low copy numbers (20 and 17 IU/ml) RT‐PCR positive amongst these. This finding is in agreement with several other studies with HBV DNA positivity in isolated anti‐HBc cases (0–0·91%). Conclusion: About 0·77% DNA positivity (2/259 isolated anti‐HBc positive) by alternate PCR missed by ID‐NAT underlies the fact that anti‐HBc (Total) testing continues to be relevant in context of enhancing blood safety, especially in medium endemicity region like India. It is also possible to adopt screening algorithm of Japan Red Cross where units are considered transfusable if the anti‐HBs titre is over 100 mIU/ml, and we could have used 35·3% of repeat reactive anti‐HBc units using this approach.